Impact of reclamation on fishery activities in Malaysia - Jumain, Nora Azura; Kamarulzaman, Nitty Hirawaty; Abd Latif, Ismail; Md Yusoff, Fatimah (IJAEB Research Publishing, 2018)
Reclamation activities are the process of creating new land from the ocean,lake and riverbeds with the aim of overcoming the scarcity of land needed for development.While the reclamation activities would benefit the society,the process could pose certain disadvantages to the residents in the area.Thus, the main purpose of this study was to determine the perception of fishermen towards reclamation activities at Merambong Shoal and the reclamation impact towards their income and fish catch.A structured questionnaire was used as a research instrument to collect the data of 79 fishermen who are actively fishing at Merambong Shoal.Descriptive analysis,paired sample t-test,and mean ranking analysis were used to analyze the data collected.The result in mean ranking analysis revealed that the majority of the fishermen had a negative perception towards the reclamation activities.Paired sample t-test analysis revealed that after the reclamation occurred,fishermen experienced a decrease in total income with a mean value of RM1,967.72 as well as fish catch with a mean value of 12.849kg.It is therefore important that relevant authorities preserve,and improve the Merambong Shoal ecosystem;also good management practices are needed to ensure that the number of fish catches will not be further affected by the reclamation activities.